Ayeen Akbery, Volume 1 Or, The Institutes of the Emperor Akber - Abu-'l-Faḍl Ibn-Mubārak 1551-1602 (Cambridge library collection. South Asian history, 1783)
Akbar the Great (1542–1605) is often regarded as the Mughal Empire's most accomplished ruler. This document on the workings of his empire was produced by Akbar's vizier, Abu'l-Fazl ibn Mubarak (1551–1602). Between 1783 and 1786, the scholar Francis Gladwin (1744/5–1812) produced an English translation from the original Persian. Reissued here is the two-volume edition that appeared in 1800. As the work's dedicatee and Governor-General of Bengal, Warren Hastings had seen the translation as illuminating the Mughal Empire's 'original constitution' and believed it would educate and inform Britain's colonial administrators. Gladwin's text would not be superseded for many decades, and it testifies to the quality of his scholarship and the contemporary concerns of the East India Company. Volume 1 explains the workings of the royal household and military offices, including details of the mint, treasury and harem, as well as building regulations